تجليات الثورة الجزائرية داخل السجون والمعتقلات الاستعمارية 4591 4591 م - خليفي, عبد القادر (جامعة الوادي - University of Eloued, 2019)
This modest article reviews the distinguished struggle of tens of thousands of Algerians, victims of colonial prisons and detention camps, who presented illuminated paintings of resistance and challenge. They demonstrated the strength of their association with the liberation revolution and embodied the ability of the FLN to infiltrate into the occupation strongholds and turn them into camps for political formation, and schools of education, which thwarted the French strategy, and contributed to the achievement of the objectives of the struggle.
مقال
Keywords: Les prisons-Centre de détention-Algérie-Politique coloniale; السجون,المعتقلات,الجزائر,السياسة الإستعمارية,جبهة التحرير الوطنى,الثورة الجزائرية,فرنسا,النضال الجزائري